Rhodium(III)‐Catalyzed Tandem [2+2+2] Annulation–Lactamization of Anilides with Two Alkynoates via Cleavage of Two Adjacent C−H or C−H/C−O bonds. Issue 16 (9th August 2016) - Fukui, Miho; Shibata, Yu; Hoshino, Yuki; Sugiyama, Haruki; Teraoka, Kota; Uekusa, Hidehiro; Noguchi, Keiichi; Tanaka, Ken
Abstract: An electron‐deficient Cp E rhodium(III) complex bearing a cyclopentadienyl ligand with two ethyl ester substituents catalyzes the tandem [2+2+2] annulation–lactamization of acetanilides with two alkynoates via cleavage of adjacent two C−H bonds to give densely substituted benzo[ cd ]indolones. The reactions of meta ‐methoxy‐substituted acetanilides with two alkynoates also provided benzo[ cd ]indolones via cleavage of adjacent C−H/C−O bonds. Furthermore, 3, 5‐dimethoxyacetanilides reacted with two alkynoates to give dearomatized spiro compounds. Abstract : Full circle : An electron‐deficient Cp E ‐rhodium(III) complex (see picture) catalyzes the tandem [2+2+2] annulation–lactamization of acetanilides with two alkynoates via cleavage of adjacent two C−H or C−H/C−O bonds to give densely substituted benzo[ cd ]indolones. On the other hand, 3, 5‐dimethoxyacetanilides reacted with two alkynoates to give dearomatized spiro compounds.